Rising stars mathematics: teacher's guide year 2 - Cottingham, Bella; Low, Emma Moseley, Cherri (Rising Stars Wellingborough, 2016)
The Year 2 Mathematics Teacher's Guide focuses on building foundational math skills through hands-on activities and engaging strategies. Key topics include number sense, basic operations, geometry, measurement, and data handling, with an emphasis on fostering problem-solving and a positive attitude towards math. Continuous assessment and diverse resources support varied learning needs.